2022
DOI: 10.1245/s10434-022-11763-2
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Use of PlasmaJet Device During Cytoreductive Surgery for Advanced-Stage Ovarian Cancer: Results of the PlaComOv-study, a Randomized Controlled Trial in The Netherlands

Abstract: Objective Standard surgical treatment of advanced-stage ovarian carcinoma with electrosurgery cannot always result in complete cytoreductive surgery (CRS), especially when many small metastases are found on the mesentery and intestinal surface. We investigated whether adjuvant use of a neutral argon plasma device can help increase the complete cytoreduction rate. Patients and Methods 327 patients with FIGO stage IIIB–IV epithelial ovarian cancer (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…However, only the absence of ascites and peritoneal carcinomatosis during surgery, FIGO stage IIIB/IIIC and serious histology were the significant independent predictors of complete interval CRS as presented in multivariable analysis. Furthermore, use of the PlasmaJet surgical device was an independent predictor of complete CRS, which is in line with the results of the PlaComOv study [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, only the absence of ascites and peritoneal carcinomatosis during surgery, FIGO stage IIIB/IIIC and serious histology were the significant independent predictors of complete interval CRS as presented in multivariable analysis. Furthermore, use of the PlasmaJet surgical device was an independent predictor of complete CRS, which is in line with the results of the PlaComOv study [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…The extent of surgery required to achieve the outcome was also documented. These results can be found in the original article of the PlaComOv-study [ 28 ].…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In clinical practice, the effect of less tissue infiltration by using the PlasmaJet may also be reflected in the quality of life. Patients who had surgery using the PlasmaJet showed a higher quality of life six months after the procedure [ 17 ]. A possible explanation could be that less tissue damage results in a different process of tissue repair and regeneration (inflammation, proliferation by fibrogenesis and angiogenesis and remodeling).…”
Section: Resultsmentioning
confidence: 99%
“…One of the additional options during surgery is the possibility to use Neutral Argon Plasma (PlasmaJet Surgical Device of Plasma Surgical, Inc, Roswell, GA), which increases the number of complete cytoreductions. 6 Even previous studies showed that the adjuvant use of the PlasmaJet during CRS for advanced-stage EOC resulted in a significantly higher percentage of complete CRS compared with conventional treatment without the use of the PlasmaJet. [7][8][9][10] The costs of treatment of advanced-stage ovarian cancer can range from V20,000 for only surgery up to V200, 000 and even higher for treatment with both surgery and chemotherapy.…”
Section: Introductionmentioning
confidence: 97%